Comparison of chemical pregnancy rates according to the anesthetic method during ultrasound-guided transvaginal oocyte retrieval for in vitro fertilization: a retrospective study - Hyun Joo Heo; Yu Yil Kim; Ji Hye Lee; Han Gyeol Lee; Seung Min Baek; Ki Man Kim (Anesthesia and Pain Medicine, 2020)
Background Oocyte retrieval is the most important procedure in in vitro fertilization (IVF). Various anesthetic methods are used to control a patient’s anxiety and pain during IVF; however, there are no recommended anesthetic methods at present. In this study, we retrospectively investigated chemical pregnancy rates according to the anesthetic method used for oocyte retrieval. Methods We reviewed records of patients who underwent oocyte retrieval between January 1, 2012 and December 31, 2017. Patients were divided into the spinal anesthesia (SA) and monitored anesthesia care (MAC) groups. The primary outcome was chemical pregnancy rate after IVF. Results The study included 95 patients. SA was administered in 77 (81%) and MAC in 18 (19%). The overall chemical pregnancy rate was 32.6% (31/95). According to the anesthetic method, the pregnancy rate was 32.5% (25/77) in the SA group and 33.3% (6/18) in the MAC group. There was no statistical difference in the pregnancy rate between the groups (P = 0.575). The procedural time was significantly shorter in the SA group than in the MAC group (P < 0.001). Conclusions Chemical pregnancy rates were not significantly different between the SA and MAC groups. However, the procedure duration was shorter in the SA group than in the MAC group.